Pengaruh Integritas dan Kapabilitas Kerja terhadap Kinerja Pegawai melalui Profesionalisme - Aloysius Lambok Siahaan (Syntax Corporation Indonesia, 2025)
This research aimed to determine the effect of work integrity and work capability on employee performance through professionalism at Prime Customs and Excise office Type A Tanjung Priok (KPUBC Type A Tanjung Priok). This research was a quantitative method with an explanatory research approach. The instrument used in this research was questionnaire arranged on a five-point Likert scale. 293 respondents who are active employees at Prime Customs and Excise office Type A Tanjung Priok (KPUBC Type A Tanjung Priok) were taken as the sample. The data were analyzed using SEM-PLS method with SmartPLS software version 3.2.29. The results of the research using the SEM-PLS method showed that integrity had a positive and significant effect on employee professionalism and employee performance. Work capability had a positive and significant effect on employee professionalism and employee performance. Professionalism had a positive and significant effect on employee performance, and partially mediated the integrity and employee performance, and partially mediated work capability and employee performance.